Gotycyzm/gotycyzmy – rekwizyty i metamorfozy - Izdebska, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article deals with phenomena of the Gothic the most often described as a set of often-linked elements rather than a fixed genre. The text presents a variety of cultural incarnations of the convention: from the eighteenth century novel by horror movies to subcultural style of Goths. This essay also examines the basic Gothic concepts, like the uncanny and the abject, which determine the worlds depicted in Gothic narratives, especially characters who remain in close connection with the space formed as a labyrinth. Finally, the article is an attempt to answer the question about the source of the expansion of the aesthetics of the Gothic in the contemporary culture.